Estratégias didático-pedagógicas para crianças no espectro autista: as significações dos docentes mestrado em educação: Psicologia da Educação - Moreira, Marina Gomes (2024)
This research had as its guiding thread an interview carried out with a teacher from a municipal public school in the East Zone of São Paulo and aimed to understand this teacher's meanings about the didactic-pedagogical strategies developed to teach classes to children with ASD (Autism Spectrum Disorder). The foundation in Socio-historical Psychology, which is based on the theoretical-methodological assumptions of Historical-dialectic Materialism, allowed a better understanding of the movements of our historical reality, as well as the understanding of the contradictory processes of transformation intertwined there. We sought to understand the training needs to develop the activities and strategies used, trying to identify the necessary instruments, resources and materials. The reality that provokes this research is the teacher in the field in his educational process as a professional, carrying with him knowledge and experience fruits of his training - expressed in his didactic-pedagogical practice and in his intentionality in the face of the school reality and the relative diversity he faces , notably with regard to the inclusion of students with autism. The instrument used was the reflective interview. Two online meetings were held with the teacher, which generated four Meaning Nuclei, essential syntheses for the analysis process. The nuclei revealed the complexity of the educator's experience, as a mother of a child with autism and as an educator understanding school inclusion inexorably as part of teaching practice. Historically, the situation of people with disabilities has resulted in clashes in the fight for their rights: the school inclusion of students with autism is part of the ethical and moral construction of a less exclusionary and segregationist society